Living alone, living together : two essays on the use of housing - King, Peter, 1960- (Emerald Publishing Limited, 2017)
The book considers how a dwelling can protect and promote both our anxieties and our relationships. Dwelling magnifies our anxieties and allows us to reject the world, yet it is also what we need to form long and lasting relationships.The first long essay considers the one truly private space we have: inside our heads. This is the most intimate place we have, yet we are singularly unable to control it or even to know it. We cannot visualise it and we cannot determine what enters and what comes out. These leads to a discussion on anxiety and depression and how the solitude offered by private space - the head and the home - allows for anxiety to take over an individual. But it is also suggested that it is only through the privacy of a dwelling, and the intimacies that can develop here, that anxiety can be assuaged. The essay is written in a fragmentary manner to show the often contradictory or conflicting nature of our headspace: it often appears that there are many conflicting voices in our head and the essay seeks to reflect these differences.The second essay is based on the premise that our relationships come out of our private dwelling. We need the protected intimacy, the inclusion and exclusion of private dwelling in order to flourish and to grow, and if we are to live together in a fully committed manner we depend on this enclosed and excluding space. The significance our lives are spun out of this particular space. Living together expands what is mine by creating what is ours, a oneness out of two people. This closeness requires enclosure and exclusion, which allows us to nurture and protect others as well as ourselves. It is this sense of ours, which each of us holds, that allows us to be free. But this closeness can be perverted by aspiration and the controlling impulses of the ego. Living together is where we are without ego or aspiration. It is characterised rather by inwardness, complacency and stasis. And only once we have this are we able to move freely outwards into the world, knowing as we go that there is somewhere that is ours. Both essays use a non-tradition literature to explore being alone and being with others rather than relying on the social science literature. Likewise, the essays take an introspective approach that recognises the subjectivity of the relations at play here. The aim of the book is build up a distinctly new picture of dwelling and housing from first principles without any particular reliance on the existing literature and approaches.